SURVEY OF BACTERIAL BLIGHT OF SOYBEAN (Glycine max L.) CAUSED BY Pseudomonas syringae IN THE CENTRAL GEOPOLITICAL ZONE OF ADAMAWA STATE - S. M. KABIRU; F. K. CHANNYA; I. B. CHIMBEKWUJO (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY GOMBE, 2022)
A survey was conducted in two Local government areas (Girie and Yola-south) of the central region of Adamawa state during the months of August and September, 2019. 16 soybean fields were surveyed (random sampling) for recording the severity and incidence of bacterial blight of soybean. At (P=0.05), In Girie local government area, result showed high percentage severity in GREF-5 and GREF-8 having the highest value (85%) respectively, the highest percentage disease incidence was recorded in GREF-5 (79.4%). Percentage disease incidence and severity in Yola-South was also high with YLSF-2 having the highest value (71.3%) and (85%) respectively. In the central geopolitical zone of Adamawa state, the Percentage incidence is moderate with mean value of (50.0%). Percentage severity is generally high in the zone with mean value of (65.6%). In conclusion, the research indicate a high percentage disease incidence and severity of bacterial blight of soybeans in the central geo-political zone of Adamawa state.